Using Holistic and Ethical Practices with Emotional Support Animal Requests. Issue 3 (3rd July 2022) - Stewart, Leslie A.; Hakenewerth, Timothy J.; Rabinowitz, Peter; Fowler, Heather
ABSTRACT: Many professional counselors and the general public are enthusiastic and curious about the role of animals in mental health. In particular, professional counselors face a growing demand for professional consensus guidelines to ethically and appropriately respond to emotional support animal (ESA) documentation requests. In this article, the authors clarify helper animal taxonomy and discuss current literature, laws, policies, risks, and benefits relevant to making professional decisions surrounding the sensitive issue of ESAs in client wellness.